Energy Efficiency of Railway Lines - Tomislav Josip Mlinarić; Klemen Ponikvar (Promet (Zagreb), 2011)
Energy saving is necessary in accordance with the principles of sustainable development. Energy consumption is increasing, and the production capacities are limited. The three main railway segments such as: railway infrastructure, traffic management and dynamic train movement have an important impact on energy consumption for train haulage. The aim of the research presented in this paper is to determine energy consumption efficiency for train haulage, by choosing optimal construction parameters of railway lines, modern design of railway stations, optimal traffic management and energy efficient dynamic train movement. The paper gives a concrete presentation of energy consumption in all three segments of railway traffic and proposals for rationalization of energy consumption. The infrastructure managers and rail carriers should cooperate in the process of efficiency consumption of energy for train haulage. Saving of energy is a never-ending process.